Manual Didáctico En Braille Para El Aprendizaje De Inglés Básico De Los Estudiantes No Videntes De La Asociación Aprodvich De La Ciudad De Riobamba - Bravo, Luis Oswaldo Guadalupe; Montenegro, Marco Antonio Bravo; Pazmiño, Alberto Fabián Altamirano; Yerovi, Enrique Jesús Guambo; Yanez, Gabriel Isaac Orozco; Peñafiel, Marcelo Eduardo Allauca; Guadalupe, Carla Sofía Arguello (European Scientific Journal, ESJ, 2017)
The objective of the present research is the elaboration and application of a didactic manual with communicative strategies to develop Basic English for students of the Provincial Association of the Visually Impaired of Chimborazo (APRODVICH). The didactic manual seeks to provide techniques and instruments that support the Teaching Learning process of a second language according to the specific needs of the group under study. It becomes a progressive and systematic teaching instrument consisting of six units that include vocabulary activities, basic structures and use of questions that were applied in the classroom with the accompaniment of the teacher. The research has a quasi-experimental, correlational, descriptive, explanatory, applicative, field and bibliographic design. The technique of direct observation was used with the application of checklists and questionnaires reviewed and endorsed by academic peers that allowed the evaluation of the knowledge acquired in students such as spelling, pronunciation and comprehension. The sample was evaluated in two instances—pre and post—and the results were tabulated, analyzed, interpreted and contrasted which determined the progress and significant development in pronunciation, use of the verb structure To-Be and whquestions of the English language in blind students.